The Role Of Breast Cancer Survivors In Improving Breast Self Examination Practice Skills At SMAN 1 Asembagus: The Role Of Breast Cancer Survivors In Improving Breast Self Examination Practice Skills At SMAN 1 Asembagus - Faradina, Daniar; Hidayati, Ainul; Sukowati, Umi; Nafisyah, Ulfatus (Blambangan Journal of Community Services (BJCS), 2025)
Breast cancer (Ca Mammae) is the second most common cancer in women worldwide and contributes significantly to a number of deaths each year. Breast cancer can be prevented through primary prevention strategies, namely BSE. However, this is still rarely done due to factors such as inadequate knowledge, supportive attitudes, resulting in low skills to perform BSE independently. The purpose of this article is to provide health education using the experiential learning method, namely by presenting Ca Mamae survivors to improve the skills of respondents. Respondents were 61 students of grade XI SMAN 1 Asembagus Situbondo. The results obtained were: Of the 61 students who became respondents, as many as 41 students (67.2%) had good skills, 19 students (31.1%) had sufficient skills, and only 1 student (1.6%) had poor skills. This shows a significant increase in students' skills regarding BSE after being given health education. This is because using this method that combines cognitive, emotional, and practical aspects is proven to strengthen students' understanding and make information more meaningful and easier to remember. Keywords : Ca mamae, BSE, Skills